Profil protein total, albumin dan globulin pada ayam broiler yang diberi kungiy, bawang putih dan Zinc (Zn) - Sus Derthi Widhyari; Anita Esfandiari; . Herlina (Jurnal Ilmu Pertanian Indonesia, 2011)
The objective of this experiment was to study the effectiveness of turmeric, garlic and zinc supplementation on protein, albumin and globulin concentration of broiler. One hundred DOC were divided into five treatments, four replications, consist of five chicks in each replicate. The treatments were RO (basal diet as a control), R1 (RO + 1,5% turmeric powder +2,5 % garlic powder), R2 (RO + 2,5% garlic powder + 120 ppm zinc), R3 (RO +1,5% turmeric powder+ 120ppm zinc) and R4 (RO +1,5 turmeric powder+ 2,5% garlic powder + 120 ppm zinc). The diet contain 23,5% crude protein and 3215 kcal metabolizable energy. Blood samples were taken from axillary veins at the three and six weeks of age. The results showed that total protein and globulin concentration at 6 weeks slightly higher than 3 weeks old chicks but not significantly different (P>0.05). Albumin concentration were highest on R3 treatment. Total protein and globulin concentration washighest on the R2 treatment. In conclusion, the supplementation of garlic (2.5%) and ZnO (120 ppm) showed the best combination to improve immune response in broiler.